A dual-function SMES-based series-connected compensator of dynamic voltage restoration and fault current limitation for photovoltaic microgrid. (November 2022) - Li, Youjin; Jin, Jianxun; Wang, Lina
Abstract: A dual-function series-connected compensator based on superconducting magnetic energy storage (SMES-based SCC) is proposed for a photovoltaic microgrid. The SMES-based SCC can operate in two different modes: dynamic voltage restorer for voltage fluctuation and fault current limiter for short-circuit fault. The SMES provides/absorbs power to/from the common DC-link capacitor by a DC/DC converter under different modes with fast response speed. In order to achieve better tracking performance to reference voltage and overcome the drawback of the conventional control methods, a modified sliding mode controller based on SVPWM strategy (SMSVM) is proposed for control of the SCC. The performances of the SMES-based SCC under different operation modes are evaluated through a series of simulation results and its superiority is verified by comparing it to a battery energy storage-based SCC. Simulation and comparative analyses between the proposed SMSVM method and the conventional hysteresis control method are conducted to prove the validity and superiority of the SMSVM method.